Comprehending the role of individual microstructural features on electrochemical response and passive film behaviour in type 304 austenitic stainless steel. (March 2021) - Pradhan, S.K.; Bhuyan, P.; Bairi, L.R.; Mandal, S.
Graphical abstract: Highlights: Individual role of microstructural features on passive film resistance is studied. Higher donor densities in the sensitized specimen impaired its film resistance. Greater film resistance in coarse-grained specimen is attributed to the lower GBSA. The defects formed during straining deteriorate the protectiveness of passive film. Lower defect density in GBE specimen is ascribed to higher fraction of Σ3+Σ9+Σ27. Abstract: The individual implication of sensitization, grain size, residual strain, and grain boundary character distribution on semiconducting response of passive film in 304 stainless steel is investigated. Involvement of higher donor densities in the sensitized specimen deteriorated passive film stability. The greater density of random grain boundaries in fine-grained specimen promoted the defects formation in the passive film. In contrast, higher fraction of 'special' boundaries and triple junctions, realized through grain boundary engineering, suppressed the formation of defects in the passive film. Interestingly, defects induced via straining accelerated the oxygen vacancy formation at metal/film-interface, which depreciated the protectiveness of passive film.